Legal Review of Implementation of Cooperation Agreements between Agents and Distributors in Business Law Principles - Muhammad Sofwan; Rokilah (Warmadewa Press, 2024)
This study examines the cooperation agreement between agents and distributors in the distribution of 3 kg Liquefied Petroleum Gas (LPG). A law consists of regulations that govern society, and a treaty is an agreement where parties commit to certain obligations, ensuring legal certainty and justice. LPG, typically a colorless and odorless fuel, is crucial for various domestic and international uses. The research focuses on how well the Agent-to-Distributor cooperation agreement is being implemented and the legal consequences if the distributor fails to comply with it. Using empirical legal research methods, the study gathers relevant data and analyzes the effectiveness of the cooperation agreement. The findings indicate that the implementation of the agreement is generally in line with the written terms. However, if the distributor does not adhere to the agreement, they may face legal penalties, including sanctions and fines. This research highlights the importance of contractual agreements in ensuring smooth LPG distribution and the need for compliance to avoid legal repercussions.